MENINGKATKAN KINERJA PROTOKOL ROUTING AOMDV UNTUK MENCARI RUTE BERDASARKAN PERGERAKAN NODE DAN MENGURANGI BROADCAST STORM DALAM JARINGAN MANET - Mei Sukriani; Andy Hidayat Jatmika; Raphael Bianco Huwae (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
Rapid topology changes in Mobile Ad Hoc Networks due to node movement often cause network instability. Each node in the network can move freely with varying speeds in different directions. As a result, the connection between devices can be disconnected or reconnected depending on the different communication ranges. Node movement causes constraints on the communication path created by AOMDV, because it does not take into account node mobility, so AOMDV has difficulty in maintaining route stability. This study aims to improve the performance of the AOMDV routing protocol in MANET by using the TimePrediction algorithm to improve the calculation of node movement during the route search process. This approach involves modifying the